Employing spatial queries in Qgis: identifying and evaluating potential sites for forest nurseries installation in the Limassol district - Koumoulidis, Dimitrios; Varvaris, Ioannis; Hadjimitsis, Diofantos G. (My University, 2025)
Geographic Information Systems (GIS) are a modern tool for managing, analyzing, and processing spatial and temporal data. This technology ensures secure and reliable data while maintaining a steady and valid flow of information. The proficiency in utilizing GIS has enabled modern societies to draw precise and rational conclusions, particularly when various decision-making centres are called upon to engage with phenomena, processes, and activities intricately connected to the broader economic and social dimensions of human activity. Integrating GIS into the comprehension, prediction, analysis, and surveillance of forest fires in science has for many years, fostered collaboration among diverse socioeconomic stakeholders, including governmental bodies, academic institutions, and various organizations, to address this devastating issue. As a cause-causation of climate change, forest fires are the dominant threat to Cypriot forests. Given the sluggish natural regeneration of the island's forests, primarily caused by climatic constraints, steep terrain, and inadequate moisture and precipitation, there is an urgent need to implement artificial reforestation strategies. This study seeks to identify and define suitable locations for establishing and managing nurseries in the Limassol district, which local forestry services and various public or private entities can leverage. The optimal selection of nurseries guarantees a reliable supply of plant resources to entities participating in activities and initiatives aimed at the artificial regeneration of Cypriot forests. Such nurseries are envisioned to facilitate future reforestation projects while fostering economic growth and activity among the mountain and peri-urban populations. The study's workflow is within the Qgis free software environment, leveraging satellite imagery from the Limassol provincial unit, the latest Land Use Cover maps, Digital Elevation Model (DEM) maps, and maps of ecologically vulnerable areas and regions under conservation protection. Data regarding the hydrographic and road networks of the examined area are also employed. The conclusive selection of viable locations involves environmental criteria related to the cultivation of native forest species, such as Pinus nigra var. pallasiana and Pinus brutia (Calabrian pine), as well as factors that facilitate the seamless and continuous operation of the nurseries. Findings from the study demonstrate that the ideal areas for establishing and managing nurseries in the wider Limassol district are confined to the northern mountainous massif. These areas are scattered and vary in size, situated within zones of existing forest ecosystems and accessible through the current road network alongside the existing hydrographic network. This study aspires to be an integral part of the framework for forthcoming assessments and evaluations, focusing on identifying suitable areas for rational grazing, pasture farming, sustainable hunting, and agrotourism, as well as selecting prime locations for establishing tourist units.
Keywords: Qgis; Optimal land use selection; Spatial Planning; Remote Sensing; Forest artificial regeneration; Limassol; Cyprus